Logística agroindustrial: grãos brasileiros cultivados na região Centro - Oeste - SILVA, Jonathan Pereira da (137, 2023)
Este trabalho tem como principal objetivo discutir a Logística Agroindustrial, no Brasil. Para isto será utilizada estudos e pesquisas referentes a este processo. Dessa forma, serão apresentados como os processos Logísticos no setor Agro no Brasil e Região Sudoeste, fundação da logística neste setor, qual a importância da exportação de grãos e outros produtos fornecidos pelo agro, na economia, logística de movimentação nacional destes produtos, logística de armazenamento.

The main objective of this work is to discuss Agro industrial Logistics in Brazil. For this, studies and research related to this process will be used. In this way, they will be presented as the Logistic processes in the Agro sector in Brazil and Southwest Region, foundation of the logistic in this sector, what is the importance of the export of grains and other products supplied by the agro, in the economy, logistics of national movement of these products, logistics of storage.
Agro-Industrial logistics: brazilian grains grown in the Central-West region
Keywords: Áreas agroindustriais; Produtos; Logística; Gestão e Negócios